Toward a more sustainable environment: Understanding why and when green training promotes employees' eco‐friendly behaviors outside of work - Usman, Muhammad; Rofcanin, Yasin; Ali, Moazzam; Ogbonnaya, Chidiebere; Babalola, Mayowa T. (Human Resource Management, 2023)
AbstractAlthough green training has been shown in past research to promote environmentally responsible behaviors at work, scholars have paid less attention to its influence on employees' eco‐friendly behaviors outside of work. This omission is critical because confining green training research to the work domain obscures its benefits in promoting employees' pro‐environmental behaviors beyond the workplace, and thus its role in supporting organizational efforts to conserve the natural environment. To address this gap, we examine the direct and indirect (via connectedness to nature) relationships between green training and employees' eco‐friendly behaviors outside of work, including consumption of eco‐friendly products, reuse of items and materials, and reduced consumption of resources such as water, electricity, and paper. We also examine the moderating influence of intrinsic spirituality on the direct link between green training and connectedness to nature, as well as the indirect link between green training and eco‐friendly behaviors beyond the workplace. Using time‐lagged, multisource data, we find support for our hypotheses. Our findings advance knowledge on the important yet largely overlooked role of green training in shaping employees' environmentally responsible behaviors outside of the workplace.